1988
DOI: 10.1128/mcb.8.9.3676
|View full text |Cite
|
Sign up to set email alerts
|

Promoter sequences required for transcription of Xenopus laevis histone genes in injected frog oocyte nuclei.

Abstract: Amphibian oogenesis is accompanied by the accumulation of histone mRNA and proteins in the absence of ongoing DNA replication. To begin an analysis of the mechanisms by which histone gene expression is regulated during frog oogenesis and embryogenesis, we used oocyte injection to examine the upstream sequences required for transcription of genes encoding each of the five histone classes. We found that sequences necessary for maximal levels of transcription are located 100 to 200 base pairs upstream of the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…(3) A single copy of the U1 snRNA gene repeat containing the U1b1 and U1b2 genes (Lund et al 1987) was used because amphibian coiled bodies contain minor amounts of the U1 snRNA (Wu et al 1991); additionally the U1 snRNA injection serves as a control for characteristics shared by the U7 snRNA and other U snRNAs. Previous work has shown that genes with functional promoters are transcribed when injected into oocyte nuclei (Trendelenburg and Gurdon 1978;Bakken et al 1979;Lund et al 1987;Heindl et al 1988). To test whether the newly transcribed U1 and U7 snRNAs were being assembled into snRNP complexes, cell extracts from oocytes injected with [α-32 P]GTP and either the U1 or U7 gene cluster, or from control oocytes injected with [α-32 P]GTP alone were immunoprecipitated with mAb Y12, which binds to the snRNP complexes but not to naked snRNAs (Lerner et al 1981).…”
Section: Resultsmentioning
confidence: 99%
“…(3) A single copy of the U1 snRNA gene repeat containing the U1b1 and U1b2 genes (Lund et al 1987) was used because amphibian coiled bodies contain minor amounts of the U1 snRNA (Wu et al 1991); additionally the U1 snRNA injection serves as a control for characteristics shared by the U7 snRNA and other U snRNAs. Previous work has shown that genes with functional promoters are transcribed when injected into oocyte nuclei (Trendelenburg and Gurdon 1978;Bakken et al 1979;Lund et al 1987;Heindl et al 1988). To test whether the newly transcribed U1 and U7 snRNAs were being assembled into snRNP complexes, cell extracts from oocytes injected with [α-32 P]GTP and either the U1 or U7 gene cluster, or from control oocytes injected with [α-32 P]GTP alone were immunoprecipitated with mAb Y12, which binds to the snRNP complexes but not to naked snRNAs (Lerner et al 1981).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the activity of the octamer motif in the context of the intact H2A-H2B gene pair, transcription of promoters containing single and double mutations was analyzed as previously described (16), except that the H2A gene and the H2A-proximal portion of the intergenic region were included (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Exonuclease deletions and site-specific mutations were prepared as described elsewhere (19). The histone H1, H2A, and H2B constructs used in this study contain a synthetic, in-frame linker (EcoRI for H2A and H2B and BamHI for H1) within their coding regions to allow transcripts from injected templates to be distinguished from endogenous mRNAs (16). To prepare 5Ј deletions, linker-scanning mutants were digested at the Asp 718 site that was generated by linker scanning mutagenesis and an upstream site (BamHI for H2A and SalI for H2B).…”
Section: Methodsmentioning
confidence: 99%
“…The histone genes used in these studies contain synthetic in-frame linkers that allow transcripts from the exogenous genes to be distinguished from those of the endogenous genes (18). All of the H2B mutant templates except the double mutants have been previously described (21).…”
Section: Methodsmentioning
confidence: 99%